Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1002/crat.2170290527
|View full text |Cite
|
Sign up to set email alerts
|

Comparative optical absorption and photoreflectance study of n‐type CuInSe2 single crystals

Abstract: Optical absorption spectra in the photon energy range from 0.4 to 1.2 eV and photoreflectance spectra in the range of the fundamental edge are measured on n-type CulnSe, single crystals. Photoreflectance spectroscopy yields the true gap energy while the near-edge absorption spectra are dominated by acceptor -to -conduction band transitions, the acceptor ionisation energy being about 80 meV. Based on intrinsic defect chemistry considerations this acceptor is ascribed to copper vacencies.An n-leitenden CuInSe,-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…As the temperature in the experiment is reduced, the fundamental absorption edge shifts toward higher energies, as is typical for straight band CIGS semiconductors. The optical absorption coefficient α(hν) was calculated using the formula [16] …”
Section: Introductionmentioning
confidence: 99%
“…As the temperature in the experiment is reduced, the fundamental absorption edge shifts toward higher energies, as is typical for straight band CIGS semiconductors. The optical absorption coefficient α(hν) was calculated using the formula [16] …”
Section: Introductionmentioning
confidence: 99%
“…These compositions correspond to those of 23.0 to 24.0 at.% copper, 26.0 to 27.0 at.% indium and 49.5 to 51.0 at.% selenium of the thin films used in related previous investigations (NOUFI, CAHEN). It has been found that single crystals with compositions in this range can be both p-type and n-type conducting (ZEGADI et al 1992) in dependence on the specific intrinsic defect equilibrium (for a discussion of this point see YAKUSHEV et al 1994~). For the present study we selected n-type conducting samples that are converted to p-type conductivity as the result of annealing in air at sufficiently high temperatures (NOUFI et al 1986(NOUFI et al , 1987.…”
Section: Resultsmentioning
confidence: 99%
“…В области 1.0-1.4 эВ измеренный коэффициент оптического отражения тонких пленок R ~ 0.15. Коэффициент поглощения рассчитан по формуле [22]: На рис. 3 показаны спектры ФЛ необлученной и облученных пленок CIGSe, зарегистрированные при 20 К и низком уровне возбуждения ~3 Вт/см 2 излучением лазера с = 532 нм.…”
Section: стимулированное излучение и структурные характеристики 249unclassified